Directive Speech Act Analysis in the Utterances Expressed in the Pixels (2015) Movie - Singal, Christian Immanuel Joseph; Ambalegin, Ambalegin (Asosiasi dosen IDEBAHASA KEPRI, 2023)
The objective of this study was to identify the various forms of directive speech acts in the movie Pixels (2015) by applying Searle's theory of speech act. The researchers employed a qualitative method to analyze the movie's conversation for directive speech acts. The investigation focused on the different acts of directive speech acts presented in the movie. The data for the research were obtained through non-participatory observation of the movie's conversation dialogue. Each statement in the dialogue was found to contain a distinct form of directive speech act. The researchers used an identity method to analyze the data and identified 15 instances of directive speech acts, which were classified into different acts including asking (5 instances), permitting (3 instances), requesting (4 instances), begging (2 instances), and commanding (1 instance).